Postobstructive pulmonary edema following accidental near-hanging - Berdai, Adnane Mohamed (International Scientific Literature, Inc., 2013)
Patient: Female, 14 Final Diagnosis: Postobstructive pulmonary edenma Symptoms: Chest indrawing • bilateral pulmonary crepitations • tachypnea Medication: — Clinical Procedure: Controlled ventilatory support • positive end expiratory pressure Specialty: Intensive care OBJECTIVE: Unusual clinical course BACKGROUND: Postobstructive pulmonary edema (POPE) is a life-threatening complication that occurs after the relief of an upper airway obstruction. POPE occurs rarely in children, primarily after non-lethal hanging. CASE REPORT: We report the case of a 14-year-old girl who developed POPE after accidental near hanging. She had chest in-drawing, the SpO2 was 81% on room air, and pulmonary auscultation revealed bilateral crepitations. The chest x-ray showed bilateral diffuse infiltrates consistent with pulmonary edema. The intensive care management consisted of controlled ventilatory support with high-level positive end expiratory pressure. On the third day of hospitalization, the patient was weaned from the ventilator and extubated with a full recovery. CONCLUSIONS: This case confirms the importance of early recognition of POPE and the value of adapted treatment, which can lead to a favorable outcome and full recovery in cases of near hanging.